ســـرطانـة المعــدة الغديــة (Latakia University Journal -Medical Sciences Series, 2019)
تعد سرطانة المعدة الغدية من الآفات المعروفة في جميع أنحاء العالم، فهي تشكل حوالي 95% من مجمل سرطانات المعدة، وهي عادة لا تكشف إلا في مراحلها المتقدمة, مما يجعل إنذارها سيئا جداً علماً أنها قد تشاهد عند الشباب وبمرحلة متقدمة منها –وخاصة- إذا كانت هناك قصة عائلية ولكنها أكثر وجودا ما بين العقدين الرابع والسادس وهذا ما أكدته دراستنا التي أجريت في مشفى الأسد الجامعي باللاذقية على /84/ مريضاً في الفترة الواقعة ما بين عامي 1993-2003م. أكثر الأعراض شيوعاً حسب دراستنا هي: -        القهم ونقص الوزن . -        وتلاهما في المرحلة الثانية الألم البطني والقياء.   و80% من المرضى كشفت عندهم الآفة وهي في المرحلة الثالثة والرابعة  Stage III+IV. ولم تجر الجراحة الجذرية إلا فقط لـ 35% من مجموع المرضى العام بسبب انتشار الورم وعدم جدوى الجراحة الجذرية. ورغم ذلك فالإنذار عند المرضى الذين راجعوا المشفى لم يكن مشجعاً، كما أننا لم نتمكن من متابعة جميع المرضى. Gastric adenocarcinoma is considered as a widely common disease all around the world. It forms about 95% of all gastric cancers, and it is usually not discovered until reaching its last (advanced) stages which makes its prognosis so bad. Gastric adenocarcinoma could be found in an advanced stage in cases with young people specially if there is a familial history but it is most popular between the fourth and the sixth decades this was confirmed by our research which was conducted in Al-Assad University Hospital in Lattakia on /84/ patients in the period between 1993-2003. The most frequent symptoms according to our research are: • Anorexia – weight loss.• Then came the abdominal pain and vomiting 80% of the patients were diagnosed at stages III + IV.   The radical surgery was not proceeded (carried on) except in 35% of the total number of the patients because of the spreading of the tumor, and the uselessness of making  radical surgery. Despite that, the prognosis of the patients who were admitted to the hospital was not encouraging. besides that we could not follow up all the patients.